The changing ecology of primate parasites: Insights from wild‐captive comparisons. Issue 7 (2nd July 2019) - Herrera, James P.; Chakraborty, Debapriyo; Rushmore, Julie; Altizer, Sonia; Nunn, Charles
Abstract: Host movements, including migrations or range expansions, are known to influence parasite communities. Transitions to captivity—a rarely studied yet widespread human‐driven host movement—can also change parasite communities, in some cases leading to pathogen spillover among wildlife species, or between wildlife and human hosts. We compared parasite species richness between wild and captive populations of 22 primate species, including macro‐ (helminths and arthropods) and micro‐parasites (viruses, protozoa, bacteria, and fungi). We predicted that captive primates would have only a subset of their native parasite community, and would possess fewer parasites with complex life cycles requiring intermediate hosts or vectors. We further predicted that captive primates would have parasites transmitted by close contact and environmentally—including those shared with humans and other animals, such as commensals and pests. We found that the composition of primate parasite communities shifted in captive populations, especially because of turnover (parasites detected in captivity but not reported in the wild), but with some evidence of nestedness (holdovers from the wild). Because of the high degree of turnover, we found no significant difference in overall parasite richness between captive and wild primates. Vector‐borne parasites were less likely to be found in captivity, whereas parasites transmitted through either close or non‐close contact, including through fecal‐oral transmission, were more likely to be newly detected in captivity. These findings identify parasites that require monitoring in captivity and raise concerns about the introduction of novel parasites to potentially susceptible wildlife populations during reintroduction programs. Abstract : The possible changes in parasite communities between wild and captive primates. HIGHLIGHTS: Changes in host environments—from wild to captive—can lead to changes in parasitism; studying these changes can inform captive wildlife management, wildlife relocation programs, and zoonotic disease risk assessment. Comparing 22 species of primates, we found high parasite species turnover in captive hosts, but no overall difference in parasite richness between wild and captive populations. Captive primates had fewer vector‐borne parasites and appeared to gain parasites transmitted via environmental exposure and close contact. Parasitism is an important consideration in translocating primates from the wild, and in reintroduction programs, owing to the potential for novel parasite transfers into human and wild primate populations.